Postpartum Hemorrhage in a High Birth Rate Region: Epidemiological Analysis and Evaluation of Clinical Practice - Ibrayeva, Damira E; Kurmanova, Almagul’ M; Nurkhasimova, Raushan G; Ayazbekov, Ardak K; Mirzakhmetova, Dinara D; Kulbayeva, Saltanat N; Nazarbayev, Nursultan N; Dzheksembekova, Alfiya Y; Tazhibayeva, Karlygash N; Sadykova, Assel D (Bangladesh Journal of Medical Science, 2025)
Aim Postpartum hemorrhage (PPH) is a frequent complication in obstetric practice and a leading cause of maternal mortality, especially in high-birth-rate countries. Many women who survive such hemorrhages lose their reproductive potential due to radical surgeries such as hysterectomy. Objective To assess the prevalence, causes, treatment methods, and outcomes of massive postpartum hemorrhage in a high-birth-rate region. Materials and Methods A retrospective analysis of 287 cases of postpartum hemorrhage over a 5-year period (from January 1, 2018 to December 31, 2022) was conducted. All PPH cases were divided into two groups and compared by perinatal and obstetric risk factors in the Turkestan region of Kazakhstan. The frequency and prevalence of PPH, predisposing risk factors, perinatal complications, and extragenital diseases were assessed. Methods of managing postpartum hemorrhage were evaluated. Results The incidence of postpartum hemorrhage was 6 per 1,000 births, and the rate of massive transfusions was 13 per 10,000 births in the high-birth-rate region of Turkestan. The main causes were uterine atony (71.8%) and placental pathology (20.2%). Oxytocin was administered in 95.5% of cases, misoprostol in 37.9%, and tranexamic acid in 32.4%. The B-Lynch suture was the most common surgical method (32.8%), mostly in cases of uterine atony. Hysterectomy was performed in only 4.9% of cases, and in 71.4% of them the cause was uterine atony (rarely placental pathology or abruption). Conclusions Among 287 women with PPH, 62 (21.6%) had adverse maternal outcomes; of these, 14 (22.6%) underwent hysterectomy. In 88.7% of adverse outcomes, two or more predisposing factors were present. The use of organ-preserving procedures such as B-Lynch sutures, O’Leary uterine artery ligation, and temporary compression sutures reduced the hysterectomy rate by fourfold. BJMS, Vol. 24 No. 04 October’25 Page : 1172-1180